Risk of contralateral anterior cruciate ligament injury due to kinesiophobia: A narrative review: Risk of CACL injury due to kinesiophobia - Julio Zago,; G. Santos, Eros; S. Silva, Hugnaton; Rondinel, Tatiana; Queiroz, Rogério; Pivetta, Renan; Nascimento, Leonardo; Amatuzzi, Fellipe; Drummond, Adriano; Chiappa, Gaspar (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Fear of movement after a primary anterior cruciate ligament (ACL) rupture has been a risk factor for the emergence of a contralateral anterior cruciate ligament (CACL) injury. Objective: Investigate the relationship between kinesiophobia and CACL. Methods: This is a narrative review that investigated the relationship between kinesiophobia and CACL injury. The search for articles was performed in the digital databases Pubmed, Cochrane, Lilacs, Pedro and Web of Science, published in any language over a ten-year period. Articles that evaluated and followed athletes with kinesiophobia who returned to sport were included. Results: A total of three articles were eligible for analysis, with two showing a relationship between high kinesiophobia in patients who ruptured the ACL, while one study showed no differences between kinesiophobia in patients who ruptured the ACL compared to athletes without injury. Conclusion: This study demonstrated that athletes who have a high level of kinesiophobia during ACL reconstruction surgical recovery have a moderate risk of rupture of the CACL.